THE RELATIONSHIP BETWEEN THE > 25 YEARS OLD WOMEN’S KNOWLEDGE ON CERVIX CANCER AND THE PAP SMEAR TEST UNDERTAKING BEHAVIOR IN OBGYN POLYCLINIC OF BANGIL LOCAL HOSPITAL OF PASURUAN - Kurnia Indriyanti Purnama Sari; Yufi Aris Lestari; Titiek Titiek Idayanti; Widya Widya Anggraeni; Siti Siti Muthoharoh; Kiftiyah Kiftiyah; Yulianto Yulianto (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Papsmear test is a means of detecting cervix cancer early that can detect the abnormal change of cervical cells. Papsmear test is actually highly recommended to every woman who has had sexual relation, but in reality many Indonesian women have not undertaken this test. Thus, majority patients come to undertake examination after they develop advanced-stage cervical cancer. This research aimed to find out the relationship between the > 25 year old women’s knowledge on cervical cancer and Papsmear test-undertaking behavior in Obgyn Polyclinic of Bangil Local Hospital of Pasuruan. The research design employed in this study was an analytical design with cross sectional approach. The population of research was all of > 25 year old women in Obgyn Polyclinic of Bangil Local Hospital of Pasuruan, while the sample consisted of 186 respondents, taken using accidental sampling. Data of knowledge was collected using close-ended questionnaire, while that of behavior was collected using observation sheet. Then the data passed through editing, coding, scoring, and tabulating processes and was tested using chi square test. The data was displayed in pie chart form. The result of research showed that 43 (23%) respondents had good knowledge, 40 (22) had adequate knowledge, and 103 (55%) had poor knowledge. In addition, 32 (17%) respondents behaved appropriately and 154 (83%) did so inappropriately. The result of chi square test showed significance value 0.000 < α = 0.05, indicating that H0 was not supported and H1 was supported. The conclusion of research stated that there was a relationship between the > 25 year old women’s knowledge on cervical cancer and Papsmear test-undertaking behavior in Obgyn Polyclinic of Bangil Local Hospital of Pasuruan. Thus, the author expected government, private, and health workers to provide much more information in many accessible media and to motivate the people to undertake Papsmear test.